Study on Variable-ratio Wind Turbine Gearbox Transmission Design Method - Zhao Kun; Song Yongle; Bai Houyi; Yin Xue; Hu Tingjun (Jixie chuandong)
The variable-ratio wind turbine gearbox turns the variable input speed into constant output speed,which is a key component for the wind turbine front-end speed control. On the basis of the transmission principle of NGW differential gear train system,several types of variable-ratio transmission mechanisms of wind turbine gearbox are studied. The corresponding expressions and boundary conditions for gear design are derived for each mechanism, and the derived expressions are verified through professional software Romax WIND. At last,the actual example is enumerated,which is helpful for the design of this type of gearbox.